ACAT-1 gene rs1044925 SNP and its relation with different clinical forms of chronic Chagas disease - Carvalho, Thaysa Buss [UNESP]; Padovani, Carlos Roberto [UNESP]; de Oliveira Júnior, Luiz Roberto [UNESP]; Latini, Ana Carla Pereira [UNESP]; Kurokawa, Cilmery Suemi [UNESP]; Pereira, Paulo Câmara Marques [UNESP]; dos Santos, Rodrigo Mattos [UNESP] (Springer Nature, 2019)
Chagas disease, caused by the protozoan Trypanosoma cruzi (T. cruzi), although discovered more than a century ago, is still a not very well-elucidated aspect. Individuals in the chronic phase of the disease may present asymptomatic clinical form or symptomatologies related to the cardiac, digestive systems, or both (mixed clinical form). SNPs (single nucleotide polymorphisms) have been identified as important markers because they constitute about 90% of the variation in the human genome. One of them is localized to the ACAT-1 gene (cholesterol acyltransferase 1) (rs1044925) and has been linked to lipid disorders. Some studies have suggested the interaction between T. cruzi and the lipid metabolism of the host. Therefore, the objective of the present study was to evaluate the association between the ACAT-1 gene rs1044925 SNP in relation to clinical manifestations in patients with chronic Chagas disease. A total of 135 individuals with chronic Chagas disease, 86 (63.7%) asymptomatic individuals and 49 (36.3%) symptomatic patients (22 with cardiac clinical form, 18 with digestive form and 9 with mixed form) participated in the study. To evaluate the polymorphism, the PCR-RFLP technique were used. There was a significant difference and a higher frequency of AA and AC genotypes (p = 0.047 and p = 0.016, respectively) of the ACAT-1 gene in asymptomatic chagasic individuals. The result suggests a protective character of the AA and AC genotypes of the rs1044925 SNP in relation to the presence of symptomatic clinical manifestations of the disease in chronic chagasic individuals.
Keywords: ACAT-1; Chagas disease; Molecular markers; Single nucleotide polymorphisms (SNPs)